Reconceptualizing children's rights in international development living rights, social justice, translations - Hanson, Karl; Nieuwenhuys, Olga (Cambridge University Press, 2013)
"Building on recent human rights scholarship, childhood studies and child rights programming, this conceptual framework on children's rights proposes three key-notions: living rights, or the lived experiences in which rights take shape; social justice, or the shared normative beliefs that make rights appear legitimate for those who struggle to get them recognised; and translations, or the complex flux between different beliefs and perspectives on rights and their codification. By exploring the relationships between these three concepts, the realities and complexities of children's rights are highlighted. The framework is critical of approaches to children as passive targets of good intentions and aims to disclose how children craft their own conceptions and practices of rights. The contributions offer important insights into new ways of thinking and research within this emerging field"--